New Qualitative Perspective in Human–Computer Interaction: Designing Mobile English for STEM - Rafiq, Karmila Rafiqah M.; Hashim, Harwati; Yunus, Melor Md (Frontiers in Psychology, 2022)
The emerging field of Human-Computer Interaction (HCI) opens up more opportunities for technology integration in language learning. Technology creates more workforce in the Science, Technology, Engineering, Mathematics (STEM) field, yet the number of STEM pursuers is declining due to poor command of the English language. There is a gap in English vocabulary for STEM, which needs a novel solution from the perspective of HCI. This study aims to explore the needs of STEM learners in creating an English language competency mobile module. The methodology used is through a qualitative study. Seven STEM learners, 17 years old, participated in semi-structured interviews. The results from the interview are divided into four main themes: 1. the importance of learning English, 2. problems of learners, 3. strategies of English language learning, and 4. learners’ readiness in using a mobile app. This study is significant for mobile app designers, English language teachers and course designers as the input will provide an overview of the STEM learners’ needs in the English language. Plus, designing a mobile app from the learners’ perspectives gives more effectiveness to HCI, rendering success to second language acquisition. Future work can design and develop a mobile app to enhance STEM learners’ English language competency based on the learners’ perspectives.